OUT BOUND TRAINING MENTORING AT PONDOK PESANTREN AL-USWAH - Ratno, Puji; Nasution, Usman; Fadli, Zen; ., Aprinawati (Journal of Community Research and Service, 2024)
Outbound is an outdoor activity. Outbound can also stimulate enthusiasm for learning. Outbound is a means of increasing knowledge gained from a series of adventurous experiences so that it can stimulate the enthusiasm and creativity of students. Out bound is considered necessary for the development of a systematic and sustainable model for student development. Through the community partnership program which will be implemented at the Pondok Pesantren Al-Uswah, it is aimed at providing knowledge about learning models that can develop the character of students through out bound training as well as making the available out bound facilities a source of income for the Pondok Pesantren. This activity aims to: 1) increase partners' knowledge about out bound training which is useful in building the character of students. 2) provide out bound facilities for partner Pondok Pesantren, 3), train partners to be able to use and create out bound programs independently. 4) make the out training program a new business for partners. Outbound training activities carried out at the Pondok Pesantren Al-Uswah have produced 20 instructors who can carry out outbound activities well in accordance with standard procedures for implementing outbound activities. This activity has also produced outbound equipment which can be used as a means to carry out outbound activities for students and other general public.